(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The fact that coal is the most widely used fossil fuel for power generation is true, but still it isalso true that the coal that is available in India is of very poor quality and has a very low calorific value.Thermal power plants that burn this coal release a significant amount of heat energy and pollutants thatare exceedingly dangerous to the environment and human health. They have a number of detrimentaleffects, such as acid rain, greenhouse effects, and global climate change. The health of pregnant womenand children, in particular, is greatly impacted by the pollution of fossil fuel combustion from thermalpower plants, which is of great concern to the developing country’s health care system. Due to the use ofcoal, oil, gasoline, diesel, and natural gas, they endure a disproportionately large burden of disease anddevelopmental disability from both environmental pollution and climate change. The poor health ofchildren and women is the disproportionately heavy financial and health burden placed on certainminorities, the young, and the poor, especially those who live in developing nations where they are mostat risk from the effects of toxic air pollutants and the Carbon dioxide-driven climate change brought onby the burning of fossil fuels. The Indian government has passed the National Clean Air Program (NCAP)(MOEF(GOI), 2019) in response to the country’s rising pollution levels and its consecutive effect on thehealth care system in India. This program outlines the long-term strategy or graded response action planintended to lower air pollution in more than 100 non-attainment cities.